Giardia duodenalis and Cryptosporidium parvum infection status among migrant workers in Peninsular Malaysia - Mohd Zain, S.N. (2017)
A cross sectional study among 388 migrant workers from five working sectors was conducted to determine the protozoan infection status in Peninsular Malaysia. Microscopy examination showed 42 (10.8%) positive with Giardia spp. and 12 (3.1%) samples with Cryptosporidium spp. PCR amplicons at the triosephosphate isomerase (tpi) gene were successfully obtained for Giardia duodenalis from 30 (30/42; 71.4%) samples with assemblages AII and B in 13 (13/30; 43.3%) and 17 (17/30; 56.7%) samples, respectively. While nine samples were identified as Cryptosporidium parvum using PCR-RFLP analysis. The presence of pathogenic G. duodenalis and C. parvum in the study population highlights potential risks of foodborne and waterborne infection to the general public and calls for implementation of control strategies through treatment and health education.